Penguatan Pembelajaran Berbasis Literasi dan Numerasi - Rahmad , Ilmi Noor; Ayuningrum, Syamzah; Azizah, Fatma Nur; Azra, Qomaroh Adillah; Marcella, Zahra Tri (LPPM Universitas Flores, 2024)
This activity is a community service activity with the theme of strengthening literacy and numeracy learning. Literacy and numeracy are important skills that must be mastered to improve competitiveness and human resources (HR). Literacy and numeracy learning aims to make students familiar with literacy and numeracy. Literacy and numeracy skills include several concepts and strategies such as problem solving processes, examining information shown in making a decision, conveying ideas innovatively and creatively, as well as giving reasons, analyzing, solving, and formulating a problem. Literacy and numeracy are general and basic competencies, both of which are chosen because of the basic abilities or competencies needed by students, in this case strengthening literacy and numeracy-based learning is a competency that must be developed effectively. The method of implementing this community service is delivered through a webinar which is conducted online using the zoom meeting platform. In the webinar, the speakers explained about the definition, objectives, strategies, criteria and levels of competence in strengthening literacy and numeracy learning. More than 200 participants attended the webinar. As a follow-up to the webinar for teachers, students, and the general public to understand more about the material presented, and it is necessary to conduct offline workshops so that participants can find out more details and clarity about literacy and numeracy both at school and in the environment as well as examples and their direct application assisted by resource persons or a team of experts.